Colloidal quasi-one-dimensional dual semiconductor core/shell nanorod couple heterostructures with blue fluorescence. Issue 21 (21st May 2019) - Chen, Dechao; Wang, Aixiang; Li, Hongbo; Abad Galán, Laura; Su, Cong; Yin, Zongyou; Massi, Massimiliano; Suvorova, Alexandra; Saunders, Martin; Li, Ju; Sitt, Amit; Jia, Guohua
Abstract : ZnS (short arms)–ZnSe (long arms)/ZnS shell nanorod couple heterostructures was prepared and over-coated by a CdS layer to generate blue emission. Abstract : Herein we report a nanorod couple heterostructure made of dual semiconductors, in which two parallelly aligned ZnSe nanorods are connected by the growth of ZnS on both end and side facets, producing hetero-ZnS (short arms)–ZnSe (long arms)/ZnS shell nanorod couples. As evidenced by electronic structure studies, both experimental and theoretical, such core/shell nanorod couple heterostructures can act as a platform to precisely tailor the quantum confinement of charge carriers between the constituting components within a single nano-object, generating blue fluorescence after the overgrowth of an alloyed ZnCdS layer on the heterostructures. We foresee the mechanistic insights gained and electronic structures revealed in this work would shed light on the rational design of more complex heterostructures with novel functionalities.